The The Role of ICT Initiatives in Enhancing Urban Agriculture: A Case Study of Bengaluru Smart City - R, Mithun; S, Roopadarshini (International Journal of Social Service and Research, 2024)
Urban agriculture is gaining significance in the sustainable development of rapidly growing cities like Bengaluru, with a particular emphasis on leveraging Information and Communication Technology (ICT) for its enhancement. This paper investigates how ICT initiatives can bolster the productivity, sustainability, and inclusivity of urban agriculture in Bengaluru. Employing a qualitative research design, the study draws upon various data sources, including a series of interviews with key stakeholders, extensive field observations, and a comprehensive review of pertinent literature. Our findings underscore the transformative potential of ICT initiatives in addressing key challenges encountered in urban agriculture in Bengaluru, such as limited access to information, inadequate market linkages, and constrained financial resources. Specifically, we highlight ICT's role in optimizing crop management practices, fostering stronger market connections, facilitating financial access, and promoting social inclusivity within urban agricultural systems. Furthermore, this paper discusses the implications of these findings for policymakers and practitioners in Bengaluru and offers insights that extend to urban agricultural contexts beyond this region. By emphasizing the potential of ICT to revolutionize urban agriculture, this study contributes to the broader goals of sustainable urban development. Suggestions for future research directions in this domain are also discussed.